Impact of Mild Head Injury on Neuropsychological Performance in Healthy Older Adults: Longitudinal Assessment in the AIBL Cohort - Albrecht, Matthew A.; Masters, Colin L.; Ames, David; Foster, Jonathan K., The AIBL Research Group (Frontiers in Aging Neuroscience, 2016)
Traumatic brain injury is suggested to be a significant risk factor for dementia. However, little research has been conducted on long-term neuropsychological outcomes after head trauma. Participants from the Australian Imaging, Biomarkers and Lifestyle Study of Ageing (AIBL) who had recovered after sustaining a mild traumatic brain injury involving loss of consciousness more than five years prior were compared with matched controls across a 3-year period. Bayesian nested-domain modelling was used to estimate the effect of traumatic brain injury on neuropsychological performance. There was no evidence for a chronic effect of mild traumatic brain injury on any neuropsychological domain compared to controls. These findings indicate that individuals who have sustained a traumatic brain injury resulting in loss of consciousness, but who recover to a healthy level of cognitive functioning, do not experience frank deficits in cognitive ability.